The impact of LTE-FDD at the LTE-TDD for the co-existence under 2.6 GHz band for Malaysia - L.M. Ahmed; M.F.L. Abdullah (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
For the co-existence scenario between LTE-FDD and LTE-TDD systems, if the two systems are using an adjacent frequency carrier, there will be a need for spatial separation between the eNodeBs of the two systems, otherwise the two systems will interfere each other. The study is implemented based on realistic parameters in order to help the network designer to make a decision about the best frequency allocation and network deployments in order to achieve higher performance under the lowest possible cost. Throughout this paper, the effect of the FDD system at the TDD is evaluated under wide range of ACIR and separation distances between the two systems eNodeBs as well. The results showed that, the recommended ACIR offset by the 3GPP is not enough for the LTE-TDD uplink throughput loss ratio to be acceptable, whereas 115 dB, 45 dB, and 35 dB of the ACIR is required for the throughput loss ratio in order to drop less than 5% for the co-located, Mid-point, and Edge-point eNodeBs deployment scenario respectively. Meanwhile, comparing to the uplink case, the downlink of the TDD system is much coherent; the recommended ACIR offset is only unacceptable for the co-located deployment case, whereas 50 dB of the ACIR is required for the system to drop less than 5%.